Aeromonas caviae is the most frequent pathogen amongst cases of Aeromonas bacteremia in Japan. (April 2013) - Kimura, Muneyoshi; Araoka, Hideki; Yoneyama, Akiko
Abstract Background: Aeromonas species can cause various infections including bacteremia, gastroenteritis, cholangitis, and wound infections. To date, most studies on Aeromonas species have been reported from countries other than Japan. The aim of this study, therefore, was to evaluate Aeromonas bacteremia in Japan. Methods: We reviewed the medical records of patients with Aeromonas bacteremia from January 1994 to December 2010 in Toranomon Hospital, Tokyo, and Toranomon Hospital Kajigaya, Kanagawa, Japan. Results: Thirty-six cases of Aeromonas bacteremia were identified. Of these 36 strains, 18 were Aeromonas caviae, 13 were Aeromonas hydrophila, and 5 were Aeromonas veronii biovar sobria. The underlying diseases were solid tumor (21 cases), chronic hepatic disease (13 cases), diabetes mellitus (9 cases), hematological malignancies (4 cases), autosomal dominant polycystic kidney disease (2 cases), and aplastic anemia (2 cases). Patients with a solid tumor more frequently presented with A. caviae bacteremia than non-A. caviae bacteremia (14/18 vs 7/18; p = 0.041). Additionally, 16 of the 36 episodes were polymicrobial, and of these, 12 had stenosis or stasis of the bile duct or pancreatic duct (75%). The overall 30-day mortality was 19%. Conclusions: To the best of our knowledge, this is the first report to identify A. caviae as the most frequent causative pathogen of Aeromonas bacteremia in Japan. Additionally, compared with previous studies, most patients in our study had solid tumors. These findings suggest that the characteristics of Aeromonas bacteremia vary among study populations.